HNO‐Binding in Heme Proteins: Effects of Iron Oxidation State, Axial Ligand, and Protein Environment. (31st October 2016) - Khade, Rahul L.; Yang, Yuwei; Shi, Yelu; Zhang, Yong
Abstract: HNO plays significant roles in many biological processes. Numerous heme proteins bind HNO, an important step for its biological functions. A systematic computational study was performed to provide the first detailed trends and origins of the effects of iron oxidation state, axial ligand, and protein environment on HNO binding. The results show that HNO binds much weaker with ferric porphyrins than corresponding ferrous systems, offering strong thermodynamic driving force for experimentally observed reductive nitrosylation. The axial ligand was found to influence HNO binding through its trans effect and charge donation effect. The protein environment significantly affects the HNO hydrogen bonding structures and properties. The predicted NMR and vibrational data are in excellent agreement with experiment. This broad range of results shall facilitate studies of HNO binding in many heme proteins, models, and related metalloproteins.